Activated-Sludge Nitrification in the Presence of Linear and Branched-Chain Alkyl Benzene Sulfonates - Baillod, Charles R. (Appl Microbiol, 1968)
The effects of biodegradable linear alkyl benzene sulfonate and branched-chain alkyl benzene sulfonate detergents on activated-sludge nitrification were investigated by administering a synthetic waste containing up to 23 mg of each detergent per liter to eight bench-scale, batch, activated-sludge units. It was found that both detergents tended to promote complete oxidation of ammonia to nitrate, whereas control units produced approximately equal amounts of nitrite and nitrate. Various hypotheses are offered to explain the phenomenon.